Bridge modification proceedings of the conference "Bridge Modification" / organized by the Institution of Civil Engineers and held in London on 23-24 March 1994 - Pritchard, B. (Thomas Telford, 1995)
As the amount of traffic on our roads increases, the bridges which carry that traffic have to be modified to meet the changing demands on them. This book consists of over 20 papers covering areas of policy, design, construction, widening strengthening techniques and alternatives to strengthening. It addresses the practitioners in the industry.